2016
DOI: 10.1186/s13287-016-0428-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29 facilitates transplantation of bone marrow-derived mesenchymal stem cells to alleviate pelvic floor dysfunction by repressing elastin

Abstract: BackgroundPelvic floor dysfunction (PFD) is a condition affecting many women worldwide, with symptoms including stress urinary incontinence (SUI) and pelvic organ prolapse (POP). We have previously demonstrated stable elastin-expressing bone marrow-derived mesenchymal stem cells (BMSCs) attenuated PFD in rats, and aim to further study the effect of microRNA-29a-3p regulation on elastin expression and efficacy of BMSC transplantation therapy.MethodsWe inhibited endogenous microRNA-29a-3p in BMSCs and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Our previous results suggested that overexpression of IGF‐1 in BMSCs improved its therapeutic effect in rat uterus injury model 16. Next, we attempted to elucidate the detailed molecular events underlying this process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous results suggested that overexpression of IGF‐1 in BMSCs improved its therapeutic effect in rat uterus injury model 16. Next, we attempted to elucidate the detailed molecular events underlying this process.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous results suggested that overexpression of IGF-1 in BMSCs improved its therapeutic effect in rat uterus injury model. 16 Next, we attempted to elucidate the detailed molecular events underlying this process. It is reported that NF-jB signalling might involve in IL-10 regulation, which prompted us to examine the change of p50 subunit and potential contribution to IL-10 modulation in response to IGF-1 overexpression.…”
Section: Igf-1 Improved Bmscs Transplant Therapy In Rat Uterus Injurymentioning
confidence: 99%
“…A great many of studies highlighted that miR-29a-3p modulate BMSCs proliferation and differentiation. MiR-29a-3p facilitated transplantation of BMSCs to alleviate pelvic floor dysfunction by repressing elastin [ 4 ]. In addition, miR-29a-3p was significantly deregulated in the serum of patients with low bone mass compared with controls [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of stem cell therapy, MSCs show a multi-directive differentiation ability, whose loss of regenerative capacity lead to the impaired ability to facilitate tissue repair, thereby increasing morbidity ( 53 ). In terms of aging, taking advantage of the differentiation ability of bone marrow-derived MSCs and their secretory factors, which are beneficial for tissue repair and elastin regeneration ( 54 , 55 ) is now being considered as another alternative for vaginal prolapse to reactivate the stem cells ( 56 ). MSCs are not only able to transdifferentiate into various cell types present in the pelvic tissues and maintain collagen secretion with neovascularization but they can also deliver bioactive molecules to sites of injury to promote fibroblast proliferation and collagen synthesis ( 57 ).…”
Section: Obstacles and Outlookmentioning
confidence: 99%